Potential anti-diabetic property of the aqueous extract of the leaves of Saba senegalensis Pichon (apocynaceae) in mice - Mamadou, Dosso; Adama, coulibaly; Ousmane, Coulibaly; Doudjo, Soro; J. David, N'guessan (International Journal of Pharmacology and Toxicology, 2020)
This study made it possible to demonstrate that Saba senegalensis has hypoglycemic and anti-hyperglyvemic effects in mice. The aqueous extract of Saba senegalensis from 75 to 250 mg / Kg bw causes a dose-dependent hypoglycemia ranging from 4.84 to 34.62% (p
Keywords: Saba Senegalensis; Antidiabetic; Hypoglycemic; Antihyperglycemic; Mouse.